The Physical, Mental, Spiritual, and Environmental (PMSE) Framework for Enhancing Wellness Tourism Experiences and Its Validation in the Context of Kerala, India - Anju Kandan Parakkal; Bindu Vazhakkatte Thazhathethil; Babu George (Administrative Sciences, 2024)
Wellness tourism has emerged as a thriving sector in Kerala, India, renowned for its Ayurveda treatments, yoga, and holistic well-being offerings. However, a comprehensive framework capturing the key dimensions of wellness tourism experiences remains underexplored. This study aims to validate the physical, mental, spiritual, and environmental (PMSE) framework within the context of Kerala’s wellness tourism industry. A quantitative research design was employed, utilizing data collected from wellness tourists who participated in various wellness services in Kerala. Confirmatory factor analysis (CFA) was conducted to assess the fitness of the PMSE framework. The findings reveal that mental experience and physical experience, with their respective sub-attributes, contribute significantly to the overall wellness tourism experience. The validated PMSE framework provides valuable insights for stakeholders, enabling them to enhance the quality and competitiveness of wellness tourism services in Kerala. By prioritizing the mental and physical dimensions of wellness experiences, Kerala can strengthen its position as a leading wellness tourism destination. This study advances the theoretical understanding of wellness tourism experiences and offers practical implications for destination management and service providers in Kerala’s wellness tourism industry.